Time-resolved black carbon aerosol vertical distribution measurements using a 356-m meteorological tower in Shenzhen - Tianlin Sun; Cheng Wu; Dui Wu; Ben Liu; Jia Yin Sun; Xia Mao; Honglong Yang; Tao Deng; Lang Song; Mei Li; Yong Jie Li; Zhen Zhou (Theoretical and Applied Climatology, 2020)
Black carbon (BC) is an essential climate forcer in the atmosphere. Large uncertainties remain in BC’s radiative forcing estimation by models, partially due to the limited measurements of BC vertical distributions near the surface layer. We conducted time-resolved vertical profiling of BC using a 356-m meteorological tower in Shenzhen, China. Five micro-aethalometers were deployed at different heights (2, 50, 100, 200, and 350 m) to explore the temporal dynamics of BC vertical profile in the highly urbanized areas. During the observation period (December 6–15, 2017), the average equivalent BC (eBC) concentrations were 6.6 ± 3.6, 5.4 ± 3.3, 5.9 ± 2.8, 5.2 ± 1.8, and 4.9 ± 1.4 μg m −3 , from 2 to 350 m, respectively. eBC temporal variations at different heights were well correlated. eBC concentrations generally decreased with height. At all five heights, eBC diurnal variations exhibited a bimodal pattern, with peaks appearing at 09:00–10:00 and 19:00–21:00. The magnitudes of these diurnal peaks decreased with height, and the decrease was more pronounced for the evening peak. eBC episodes were largely initiated by low wind speeds, implying that wind speed played a key role in the observed eBC concentrations. eBC wind-rose analysis suggested that elevated eBC events at different heights originate from different directions, which suggested contributions from local primary emission plumes. Air masses from central China exhibited much higher eBC levels than the other three backward trajectory clusters found herein. The absorption Ångström exponent (AAE 375–880 ) showed clear diurnal variations at 350 m and increased slightly with height.